Thinking through fashion a guide to key theorists - Rocamora, Agnès; Smelik, Anneke 1956- (Dress cultures, 2016)
The field of fashion is now a major topic of enquiry in social and cultural theory. However, students often find it difficult to apply key social and cultural theoretical frameworks and concepts to their study of fashion. This book is designed to fill this gap for a how to think through fashion. Each chapter is a guide through the work of a selected major thinker, such as Marx, Freud, Simmel, Benjamin, Bakhtin, Barthes, Goffman, Deleuze, Foucault, Baudrillard and Butler, introducing key concepts and ideas, discussing how they have been appropriated by various authors to engage with the topics of fashion, dress and appearance, and looking at other ways in which they can be taken over to reflect on these topics.